PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI KELAS XI IPA SMAN 1 SUTERA - Silvia Yuadmiras (Departemen Matematika, 2022)
Mathematicals problem solving ability is one of the goals that must be achieved by students in learning mathematics. However, the reality was that the mathematical problem solving ability of class XI IPA SMAN 1 Sutera students is still low, as can be seen from the results of daily assessments of students who have not been able to solve mathematical problems correctly in accordance with the indicators of mathematical problem solving ability. Effort that can be made to overcome these problems are by applying the Problem Based Learning model. This type of research is a pre-experimental research with One Shot Case Study design. The purpose of this study was to describe the development of mathematical problem solving abilities of students in class XI IPA SMAN 1 Sutera after applying in the prolem based learning model. The population of this study were students of class XI IPA SMAN 1 Sutera with the research sample being students of class XI IPA 3. The research instrument used was a mathematical problem solving ability test in the form of essay questions. Based on the results of data analysis, the average mathematical problem solving ability of students is 71,41. The percentage results of each indicator on the test questions are in the capable category. Thus, it can be concluded that in general the development of student’s mathematical problem solving abilities during the application of the problem based learning model has increased. Keywords — Mathematical Problem Solving Ability, Pre-Experiment, Problem Based Learning